2011
DOI: 10.1159/000327794
|View full text |Cite
|
Sign up to set email alerts
|

Health Problems in Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency

Abstract: Following the introduction of life-saving glucocorticoid replacement 60 years ago, congenital adrenal hyperplasia (CAH) has evolved from being perceived as a paediatric disorder to being recognized as a lifelong, chronic condition affecting patients of all age groups. Increasing evidence suggests that patients with CAH have an increased risk to develop health problems during adult life, with signs and symptoms of forerunner conditions of adult disease already emerging during the time of paediatric care. Transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 187 publications
1
91
1
10
Order By: Relevance
“…It has been suggested that CAH patients develop an unfavorable cardiovascular risk profile either because of the existence of hyperandrogenism in undertreated patients, or because of the iatrogenic hypercortisolism consequent to excess glucocorticoid (31,32). Hyperandrogenism, an independent risk factor for hyperinsulinism, and iatrogenic hypercortisolism could both contribute to hyperinsulinism and insulin resistance in these patients (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CAH patients develop an unfavorable cardiovascular risk profile either because of the existence of hyperandrogenism in undertreated patients, or because of the iatrogenic hypercortisolism consequent to excess glucocorticoid (31,32). Hyperandrogenism, an independent risk factor for hyperinsulinism, and iatrogenic hypercortisolism could both contribute to hyperinsulinism and insulin resistance in these patients (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This situation may be related to smaller numbers of patients, extensive range of age distribution, and heterogeneous glucocorticoid dose among groups. Since association between children and adolescents with CAH and osteoporosis risk is not clear, follow-up and treatment plans for bone health are not well defined yet (3,19).…”
Section: Introductionmentioning
confidence: 99%
“…We have found the description of the following feelings and conditions in the literature search: shame, loneliness, fear (irreversible physical and psychological), pain, suicidal attempts, suicide, the feeling to be living with a secret, suspicion, and embarrassment (11)(12)(13)(14)(15)(16)(17). Desire of changing sex when adolescent and/or adult (gender dysphoria), depression, social phobia, social inhibitions, anxiety disorders, and panic disorders have also been described (11)(12)(13)(14)(15)(16)(17).…”
Section: Clinical Effects Of This Modelmentioning
confidence: 99%
“…Desire of changing sex when adolescent and/or adult (gender dysphoria), depression, social phobia, social inhibitions, anxiety disorders, and panic disorders have also been described (11)(12)(13)(14)(15)(16)(17). Besides these consequences, we find those which are observed and emphasized in specialized DSD clinics, such as: communication difficulties among physician, patient and family, silence pact, apparent aloofness towards medical appointments, difficult adherence to or discontinuation of treatment, etc.…”
Section: Clinical Effects Of This Modelmentioning
confidence: 99%